A comparative study on the determinants of HIV infection in Swaziland and Ethiopia. - Lokotfwalo, Vusie (My University, 2014)
Background Despite the national and international efforts to combat HIV, sub-Saharan Africa continues to suffer the effects of the pandemic. In 2011 in sub-Saharan Africa there were 23.5 million people living with the virus and 1.8 million new infections. Swaziland, with a population of 1.1 million people, has equally shouldered the HIV burden as it has an adult prevalence of 26%, which is one of the highest in the world. State resources have been affected and the number of orphaned and vulnerable children continues to rise. Ethiopia on the other hand, has a population of 74 million people and is one of the poorest countries in the world. However, the adult HIV prevalence remains low at 1.5% and is lower than many sub-Saharan African countries. HIV prevalence in pregnant women attending antenatal clinic has declined by 82% between 2000 and 2010. The main mode of transmission in both countries is through heterosexual contacts. Objective The main objective of the study was to identify and compare the main differences in the determinants of HIV infection in Swaziland (2006) and Ethiopia (2005). Materials and methods The research was a secondary analysis of a cross-sectional survey from two demographic health surveys and studied the effect of the determinants on HIV infection. We constructed a conceptual framework based on the Mosley and Chen framework, and we grouped the variables into underlying and proximate factors. The outcome variable was HIV status and descriptive statistics as well as bivariate tests were carried out using Pearson’s Chi-square and Fischer’s exact tests for associations. Univariable and multivariable logistic regression were used to model the explanatory variables against the outcome. Datasets from the two countries were then appended and propensity score matching was done using age, gender and wealth index. Further logistic regression analysis for the merged data was done for the proximate factors and the outcome. The conceptual framework based model was used to model direct and indirect determinants of HIV infection using a structural equation model. Results In Swaziland, a total of 4 584 females and 3 602 males were tested for HIV, and the adult prevalence was 26.20%. Females had a higher prevalence of 30.98% compared to their male counterparts who were at 19.51% (p<0.0001). In the multivariable regression analysis the result showed a greater than 3 times increased likelihood of contracting HIV for those who had more than 3 sexual partners in their lifetime, [AOR=3.14, 95% CI (2.55-3.87)]. Those with genital ulcers were above 2 times more likely to have HIV compared to those who did not, [AOR=2.15, 95% CI (1.71-2.71)]. Circumcision yielded almost 38% HIV protection in circumcised men compared to uncircumcised men, [AOR=0.62, 95% CI (0.45-0.85)]. In Ethiopia, a total of 5 942 females and 4 630 males aged 15-49 years were tested for HIV and the adult prevalence was 1.97%. Female prevalence was 2.39% compared to 1.43% for males (p<0.0001). In the multivariable regression analysis participants with high number of lifetime partners had almost 6 fold chance of being HIV infected compared to those who had one, [AOR=5.61, 95% CI (2.73-11.52)]. Individuals who had first sex at age 15-19 years were greater than 4 times more likely to have HIV compared to those who had never had sex, [AOR=4.20, 95% CI (1.90-9.32)]. Circumcision had HIV benefits as it yielded a 74% protection for the circumcised, [AOR=0.26, 95% CI (0.14-0.48)]. The inverse association between Moslems religion and HIV was also observed in this study as they had a 67% HIV protection compared to Orthodox, [AOR=0.33, 95% CI (0.21-0.54)]. Living in Gambela region was associated with almost 4 times increased risk of HIV infection compared to Tigray, [AOR=4.11, 95% CI (2.07-8.17)]. Analysis using logistic regression and structural equation modelling adjusting for the country effect showed a protective effect for those staying in Ethiopia compared to those staying in Swaziland. The structural equation modelling confirmed findings from the earlier regression analysis as those with age at first sex below 15 years were 6.03 times more likely to get HIV, AOR=[AOR=6.03, 95% CI (5.40-10.07)]. Those with three or more sexual partners were 5.15 times more likely to get HIV infection compared to those with one partner [AOR=5.15, 95% CI (3.77-7.03)]. Conclusion and recommendation This study was able to demonstrate the association between HIV acquisition and the determinants. Most importantly is the ability to clearly point out on the proximate factors in both countries which happen to be behavioural. The structural equation modelling added value as it was able to show the indirect factors and how they impact on HIV infection. This can be addressed through strengthening of behaviour change programs to reduce risky sexual behaviours. Programs aimed at delaying sexual debut and reduction of sexual partners should be strengthened in both countries. Male circumcision programs should be scaled up through social mobilisation and community involvement more especially in Swaziland.